Effect of social media marketing on e-commerce consumer loyalty through brand image and relationship marketing in Makassar city - Ifin Naim; Wa Ode Nursaadha Rajuddin; Ridha Taurisma Lajaria; Dzulkifri Azis Muthalib (Institute of Computer Science (IOCS), 2023)
The aim of this study is to empirically investigate how social media marketing influences social media brand image and relationship marketing in the context of e-commerce in Makassar. proposed model as well aims to examine the relationship between social media marketing, brand image, satisfaction, and trust loyalty. E-commerce industry players must be able to implement strategies to increase consumer loyalty, to compete in this industry. The strategy that can be done is to do social media marketing activity. This is because people in Makassar City are very active in using the internet and social media This phenomenon opens up opportunities for business people, especially in the e-commerce industry. The object in this study is addressed to e-commerce consumers in Indonesia. as many as 98 respondents have obtained through distributing questionnaires using non-probability sampling method. The research model is estimated using the structural transaction model with SMART-PLS. Event results that social media marketing has a significant effect on brand image and trust. Satisfaction and trust significant effect on loyalty. Furthermore, brand image has a significant effect on satisfaction, and satisfaction has a significant effect on trust. In contrast, social media marketing has no significant effect on satisfaction, and brand image has no significant effect on loyalty. This research concludes that to increase consumer loyalty in e-commerce, industry players must be able to improve product accuracy according to the description, increase responsiveness to complaints and input provided by consumers, and improve marketing activities through social media.